Transient suppression of Wnt signaling in poor-quality buffalo oocytes improves their developmental competence - Ahuja, Kriti; Batra, Vipul; Kumar, Rakesh; Datta, Tirtha Kumar (Frontiers in Veterinary Science, 2024)
The present study was undertaken to modulate the canonical Wnt (Wingless/integration) signaling pathway in the poor-quality (colorless cytoplasm after Brilliant Cresyl Blue staining, BCB-) buffalo cumulus-oocyte complexes (COCs) to improve their in vitro maturation (IVM) and embryo production (IVEP) rates. The expression of key Wnt pathway genes was initially assessed in the good (blue cytoplasm after Brilliant Cresyl Blue staining, BCB+) and poor quality (BCB-) buffalo COCs to establish a differential activity of the Wnt pathway. The Wnt pathway genes exhibited a significantly higher expression (P<0.05) in the poor-quality BCB-oocytes compared to the goodquality BCB+ oocytes during the early maturation stages. The BCB-COCs were then supplemented with the Wnt pathway inhibitor, Dickkopf-related protein 1 (DKK1) and later subjected to IVM and IVEP along with the BCB+ and BCB-controls. The cumulus expansion index (CEI), rate of nuclear maturation and embryo production, and the expression of developmentally important genes were evaluated to assess the effect of Wnt pathway inhibition on the development competence of these poor-quality oocytes. The supplementation of BCB-COCs with 100 ng/mL DKK1 effectively inhibited the expression of the key mediators of the Wnt pathway (β-catenin and dishevelled homolog 1, DVL1). A greater number of BCB-COCs (P<0.05) reached the highest scale of cumulus expansion after DKK1 supplementation and exhibited an elevated expression of oocyte maturationrelated genes vis-à-vis the BCB-control COCs. The mean percentage of oocytes in the MII stage and those reaching the morula and blastocyst stages were significantly higher (P<0.05) in the DKK1exposed BCB-COCs compared to the BCB-controls. Besides, significantly elevated expression (P<0.05) of genes implicated in germinal vesicle breakdown (GVBD) viz. AKT serine/threonine kinase (Akt), cell division cycle 25B (CDC25B), Cyclin B and embryonic genome activation (EGA) viz. eukaryotic translation initiation factor 1A (eIF1A), polyadenylate polymerase (PAP) and U2 auxiliary splicing factor (U2AF) were also observed in the DKK1-exposed BCB-COCs. These data indicate that inhibition of the Wnt pathway during the initial course of oocyte maturation can improve the development competence of poor-quality buffalo oocytes.